Greening Africa's Cities : Enhancing the Relationship between Urbanization, Environmental Assets, and Ecosystem Services - White, Roland; Turpie, Jane; Letley, Gwyneth Letley (World Bank, Washington, DC, 2017)
Africa is urbanizing late but fast. This brings many benefits but, as this report shows: thus far, urbanization in Africa, unique in a number of respects, is having deleterious and largely unchecked impacts on the natural environment; the degradation of natural assets and ecosystems within African cities carries tangible economic, fiscal and social costs; there are important opportunities to change the current environmental trajectory of African cities so that they move towards a more harmonious relationship between their natural and built environments. For this to happen, focused action is necessary.